La procrastinación académica y la autoestima en los estudiantes universitarios de la carrera de Psicopedagogía de la UNACH - Vallejo Guijarro, Paulina Geovanna (2024)
The main objective research was to analyze academic procrastination in relation to self-esteem in university students of the Psychopedagogy career, with a sample of 60 participants of third and eighth semester. Procrastination is one of the most frequent problems in the educational training communities, affecting all areas of life. The results of the research will benefit the university students to discover the root of the obstacles that prevent a potential development in the academic area as well as in other áreas necessary for social and personal functionality. The research has a methodology with a quantitative approach with non-experimental design, the type of research was basic because of the objectives; because of the place, field; because of the time, transversal; because of its level or scope, the research was correlational and descriptive. The instruments used in the study were the General Procrastination Scale and the Rosenberg self-esteem test, which facilitated the collection of relevant data. The study shows a negative and weak relationship between self-esteem and procrastination, resulting in 46% of students with high self-esteem and 48% of students with medium procrastination, allowing the deduction that procrastination on a daily basis can produce less negative impact on the formation of our worth by the unconscious construction of a negative habit, affecting in the long term, all areas of development of the people who perform it.